Challenges faced by community health volunteers in offering sexual and reproductive health care services to young women during the COVID-19 pandemic in Khwisero and Nairobi in Kenya - Mariam F. Yusuf; Mariam F. Yusuf; Mariam F. Yusuf; Washington Onyango-Ouma; Jacinta Victoria S. Muinde; Cynthia Khamala Wangamati (Frontiers in Reproductive Health)
IntroductionCommunity health volunteers (CHVs) are fundamental in many health systems across the globe. In Kenya, CHVs were essential in providing sexual and reproductive health (SRH) services during the COVID-19 pandemic. The study highlights challenges experienced by community health volunteers in Kenya while providing SRH services during the COVID-19 pandemic.MethodThe study utilized a qualitative research design to explore challenges experienced by CHVs in offering SRH services in Dagoretti North and South sub-counties in Nairobi and Khwisero sub-county in western Kenya during the COVID-19 pandemic period. We conducted 17 in-depth interviews, 7 focus group discussions, and 1 group discussion with CHVs. The data was collected in different periods: in Khwisero, November 2022–August 2023, and in Nairobi, February–April 2023.ResultsThe study's findings show that CHVs experienced several challenges while providing SRH services. The challenges included distrust by the community as a result of the interaction between anti-COVID-19 measures and other past and present health interventions such as vaccines for other diseases, insufficient personal protective gear and equipment (PPEs), limited human and financial resources to address community needs, limited and poor training on response to misinformation that led to vaccine hesitancy, and mental strain from stigma and burnout.ConclusionDuring pandemics, governments should provide adequate personal protective gear and financial and human resources for CHVs' work as they deliver SRH services to the community under risky conditions. In addition, CHVs must be trained to address misinformation about relevant medical interventions during epidemics and pandemics and provided with psychosocial support to mitigate the impact of psychological distress.